THE EVALUATION STUDY OF THE TEACHER ABILITY TO TEACHING PLANNING TOOLS ACCORDING TO CURRICULUM 2013 IN PAUD TERPADU WITRI I BENGKULU CITY - Nasirun, H.M.; Yulidesni, Yulidesni (UNIB Press, 2017)
Abstract: The purpose of the study is to describe the ability of PAUD Witri I Bengkulu City in the preparation of planning in teaching (RPPH) curriculum 2013. Types of the research used in the research si descriptive quantitative. The population in the study were PAUD Terpadu Witri I teachers Bengkulu City, the sample of the study was the total sample or sample population of all teachers (13 people) PAUD Terpadu Witri I teachers Bengkulu City, because the population less than one hundred. The results of the research are; the preparation of planning in teaching (RPPH) complied by PAUD Terpadu Witri I teachers Bengkulu City curriculum 2013 Is on the category Good enaough, but there are some things that are still lacking. Supporting advice is; there are some things that need improvement in the activities of planning in teaching (RPPH) curriculum 2013, should by fully referring to the curriculum 2013, especially in the application of scientific learning approach.Keywords: Teaching tools, curriculum 2013